Language Production in Digital Indonesian: A Psycholinguistic Analysis of Maudy Ayunda’s Instagram Captions - Sholihatul Hamidah Daulay; Fitri Aisyah Amini Nst (EXCELLENCE: Journal of English and English Education, 2026)
The rapid development of social media has significantly transformed patterns of language use and production in everyday communication. Instagram, as a visually oriented platform, encourages brief, expressive, and multimodal forms of written language through captions. This study aims to examine language production in Instagram captions written by Maudy Ayunda from a psycholinguistic perspective. Using a qualitative document analysis approach, the study focuses on sentence structure, lexical choice, code-mixing between Indonesian and English, emotional expression, and the use of emojis. The findings indicate that the captions are characterized by syntactic simplicity, frequent use of emotionally salient vocabulary, flexible bilingual language planning, and multimodal features that support efficient meaning-making. These linguistic characteristics reflect adaptive language production strategies shaped by cognitive efficiency, emotional processing, and the communicative demands of digital environments. The study contributes to psycholinguistic research by highlighting how language production operates in contemporary digital discourse.